THE EFFECT OF EDUCATION ON KNOWLEDGE, SELF MANAGEMENT BEHAVIOURS AND SELF EFFICACY OF PATIENTS WITH TYPE 2 DIABETES SYSTEMIC REVIEW - Ahmed ali Sulaiman alherbi; Husam Fahad aldabin; Saud khalaf sayil alanazi; Ahmed Saud Alharbi; Rehab Saud Alharbi; Abdulaziz Awad Alharbi; Ahmad Awad Alharbi; Basimah noor doaig almotairi; Sadan Dafr Ali Al Besher; Hussain Abdullah Al Bishr (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: The prevalence of diabetes mellitus in Saudi Arabia was dramatically increased from 3.4 % in 1996 to 19.42% in 2012 and reached to 23.9% in 2013. The Saudi Press Agency (SPA) reported that the annual cost of diabetic care and its complication is exceeding four billion Saudi Riyals. Despite of the importance of diabetic educational programs in reducing the health care expenditure and improving the quality of care. This study aimed to review the evidence regarding the impact of self-management on the outcomes of diabetic mellitus. Methods: A systematic search of articles focused on diabetes self-management education and support services was conducted. Articles were included if published between January 2013 and January 2022. We searched MEDLINE, CINAHL, EMBASE, ERIC, and PsycINFO for interventions which included elements to improve participants’ knowledge, skills, and ability to perform self-management activities as well as informed decision-making around goal setting. Results: Previous systematic reviews and meta-analyses sought to find evidence that self-management intervention using educational or behavioral strategies stimulates the individual’s performance of diabetes self-care to increase target behavior actions such as blood glucose monitoring, diet care, physical activity and medical care among adults. These studies indicated modest but significant improvements in glycemic control in educational and behavioral interventions in diabetes, although, the improvement on glycemic control seemed to decrease over time. Conclusions: The effect of self-management intervention on reduction in glycated hemoglobin seemed to be affected by baseline values of HbA1c. The higher baseline values of HbA1c, the greater the control of hyperglycemia after implementation of self-management.